Impact of supervised exercise training on systemic sclerosis with multiple organ involvement: a case report - Alhowikan, Abdulrahman Mohammed (Journal of the Pakistan Medical Association, 2022)
Supervised training exercises are the mainstay of pulmonary rehabilitation (PR) in patients with chronic lung diseases like interstitial lung disease (ILD). A 40 years old female patient with systemic sclerosis clinically presenting with usual interstitial pneumonia (UIP) and pulmonary hypertension underwent an eight-week supervised exercise training programme. Forced Vital Capacity (FVC) showed improvement from 48.7% to 54% of predicted baseline, while the initial six-minute walk test (MWT) distance also showed a considerable increase of 15.4% from the baseline after completion of the exercise training. A remarkable improvement was noticed in muscle strength for both the upper and the lower limbs. There was an increase of 79.4% right side handgrip, 25% left side handgrip, and 30.9% increase in lower limbs than baseline strength. The findings show that an exercise training programme under the supervision of trained and competent staff can benefit the improvement of lung function ---Continue